Effect of microplastics and natural microparticles on green Mussel (Perna viridis). Issue 1 (May 2021) - Putri, A R; Zamani, N P; Bengen, D G
Abstract: There are so many studies of microplastics on marine animals, but almost all of them do not compare the effect of microplastics with natural microparticles which are also can be a stressor for the animals. This can lead us to overestimate the effect of microplastics on marine animals. Therefore we conducted a study to see whether the effect of microplastics was the same as the effect of natural microparticles on green mussels ( Perna viridis ). This research was conducted experimentally in the laboratory for 21 days. Green mussels were exposed to PVC as microplastics and red clay as natural microparticles with 3 different concentrations (1.5 mg/l, 15 mg/l and 150 mg/l). We observed mortality, clearance rates, and BCI index. Clearance rates and mortality values were not statistically significant, while the BCI results showed that the effects of PVC and red clay at each concentration were only less than 10%. This suggests that the effect of microplastics and natural microparticles is similar, and it is necessary to include natural microparticles as a comparison in research related to microplastics.